Education policy implementation in Indian schools : how has the National Education Policy 2020 translated to on-ground changes? - Singaraju, Radhika (2024)
The National Education Policy 2020 (NEP 2020) was the first policy released in the 21st century in India regarding education, which proposed widespread changes in all aspects of the Indian education system. However, past policies have seen inconsistent success in the implementation due to constraints such as geographical size, population, and variability of resources across regions. This study looked at the implementation of the policy in matters related to primary school education in six schools in the National Capital Region of Delhi, India, to understand the changes in the on-ground functioning of these schools as a result of the NEP 2020, and the challenges faced and the support received during the implementation process. The data for this study was collected using ten one-on-one, semi-structured interviews with teachers, school leaders and a subject matter expert, all of whom worked in the education sector in Delhi. Translated versions of the interview transcriptions were analysed using a thematic analysis approach. The results revealed that changes had been implemented more successfully in the areas of curriculum, pedagogy, and assessment, supported by matters such as pedagogical training, than changes in the areas of academic structures and language of education, which were hampered by challenges such as infrastructure and staff shortages. The findings provide a snapshot of education policy implementation in India at the nascent phase and identify strengths and areas of improvement in the current process. They also highlight the role of various stakeholders across the education system in ensuring successful implementation. These findings can contribute to the discourse and suggest best practices that can be used to strengthen policy implementation in similar contexts